Chronic heart failure in octogenarians. Temporal trends in clinical characteristics, treatment and outcomes over two decades in a nationwide cardiology registry. (25th November 2020) - De Maria, R; Gori, M; Marini, M; Gonzini, L; Benvenuto, M; Cassaniti, L; Municino', A.M; Navazio, A; Ammirati, E; Gorini, M; Leonardi, G; Pagnoni, N; et al.
Abstract: Background: Elderly >80 years represent the most rapidly expanding population segment in Europe. Chronic heart failure (CHF) affects over 10% of this group and generates a major M&M burden. We analyzed the temporal trends in characteristics, therapy and outcomes over two decades in octogenarians enrolled in our nationwide registry. Methods: According to the recruitment epoch, among 14.283 CHF patients first enrolled in the registry since 1–1999 through 5–2018, we divided those aged 80+ (2520, 17.6%) into 3 cohorts: 1999–2005 (547, 10%); 2006–2011 (659, 16.5%); 2012–2018 (1314, 14.1%). We analyzed trends over time in characteristics, therapy, 1-year all-cause mortality and proportion admitted to hospital. Results: From 1999 to 2018 the proportion of 80+ CHF patients (60% men, 84±3 years, LVEF 41±1%, HFrEF 49%) rose from 10% to 24%. Across the 3 epochs (Table 1) we observed a shift towards the HFpEF phenotype with an increase in its driving factors (obesity, diabetes, hypertension, AFib). At the same time, the proportion treated with recommended therapies rose. Cumulative 1-year mortality did not differ across the 3 epochs (Fig.1 top), whereas the proportion of 80+ hospitalized overall, for CV causes and for decompensated HF, declined (Fig. 1 bottom). Conclusions: During 20 years, the clinical characteristics of octogenarians enrolled in a nationwide CHF registry have deeply changed, reflecting demographic variations, the evolution of CV risk factors and improved management. There was a consistent implementation of BB, MRA and devices. Survival of 80+ remained stable, but the proportion of those hospitalized for CV causes, and specifically decompensated HF, declined. These data suggest that cardiologists' input may contribute to decrease the socioeconomic burden of CHF in the elderly. Funding Acknowledgement: Type of funding source: Foundation. Main funding source(s): Fondazione per il Tuo cuore – Heart Care Foundation (HCF) ONLUS